The impact of ESG factors on purchase intention for electric vehicle ride-hailing in Vietnam - Huyen, Pham Thanh; Huyen, Nguyen Thi Minh; Quan, Tran Nguyen; Anh, Ngo Thi Phuong (Edelweiss Applied Science and Technology, 2026)
Environmental challenges such as global warming and climate change have prompted companies to adopt ESG practices to reduce carbon emissions and protect the environment. As consumers become more environmentally conscious, they increasingly evaluate firms’ ESG commitments. This study examines how ESG practices influence customers’ purchase intentions toward ride-hailing services using electric vehicles, focusing on Xanh SM, a subsidiary of VinFast. The model integrates Signaling Theory and the Theory of Planned Behavior, with mediating variables (Brand Image, Perceived Value, and Attitude) and moderating variables (Price Sensitivity and Convenience). Using a questionnaire survey of 233 participants and data analysis via SmartPLS 4.1.1.2, the findings show that ESG practices positively affect purchase intention through partial mediation of Brand Image, Perceived Value, and Attitude. However, Price Sensitivity and Convenience show no moderating effects. The study contributes theoretically by explaining customer decision-making through ESG perception and offers practical implications for businesses and policymakers promoting sustainable transportation.